Effect of dentin treatment on proliferation and differentiation of human dental pulp stem cells - Minjeong Park; Nan-Sim Pang; Il-Young Jung (Korean Academy of Conservative Dentistry, 2015)
Objectives Sodium hypochlorite (NaOCl) is an excellent bactericidal agent, but it is detrimental to stem cell survival, whereas intracanal medicaments such as calcium hydroxide (Ca[OH]2) promote the survival and proliferation of stem cells. This study evaluated the effect of sequential NaOCl and Ca[OH]2 application on the attachment and differentiation of dental pulp stem cells (DPSCs). Materials and Methods DPSCs were obtained from human third molars. All dentin specimens were treated with 5.25% NaOCl for 30 min. DPSCs were seeded on the dentin specimens and processed with additional 1 mg/mL Ca[OH]2, 17% ethylenediaminetetraacetic acid (EDTA) treatment, file instrumentation, or a combination of these methods. After 7 day of culture, we examined DPSC morphology using scanning electron microscopy and determined the cell survival rate with 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide assay. We measured cell adhesion gene expression levels after 4 day of culture and odontogenic differentiation gene expression levels after 4 wk using quantitative real-time polymerase chain reaction. Results DPSCs did not attach to the dentin in the NaOCl-treated group. The gene expression levels of fibronectin-1 and secreted phosphoprotein-1 gene in both the Ca[OH]2- and the EDTA-treated groups were significantly higher than those in the other groups. All Ca[OH]2-treated groups showed higher expression levels of dentin matrix protein-1 than that of the control. The dentin sialophosphoprotein level was significantly higher in the groups treated with both Ca[OH]2 and EDTA. Conclusions The application of Ca[OH]2 and additional treatment such as EDTA or instrumentation promoted the attachment and differentiation of DPSCs after NaOCl treatment.